Single polygon counting on Cayley tree of order 4 : generalized Catalan numbers - Pah, Chin Hee; Saburov, Mansoor (IDOSI Publications, 2013)
We showed that one form of generalized Catalan numbers is the solution to the problem of finding different single component containing single fixed root for Cayley tree of order 4. The upper and lower bounds are given for semi-infinite Cayley tree of order 4.